2016
DOI: 10.1523/jneurosci.1678-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of Rate Remapping in CA3

Abstract: The hippocampus is thought to contribute to episodic memory by creating, storing, and reactivating patterns that are unique to each experience, including different experiences that happen at the same location. Hippocampus can combine spatial and contextual/episodic information using a dual coding scheme known as "global" and "rate" remapping. Global remapping selects which set of neurons can activate at a given location. Rate remapping readjusts the firing rates of this set depending on current experience, thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…This is perhaps not surprising given that the behaviorally relevant information for the animal is not just the position along the track but also the way in which it is facing; for example this determines how far away a potential reward is, if located at one or both ends of the track. Studies using periodic tracks have shown no such global remapping, but rather some degree of rate remapping ( Schwindel et al, 2016 ), that is the direction of motion affects the shape and amplitude of place fields, but not their position. In the data we have analyzed there is very weak remapping, see Figure 7—figure supplements 1c and 2b , and so the assumption of invariance of place field to direction of motion is a good one.…”
Section: Discussionmentioning
confidence: 99%
“…This is perhaps not surprising given that the behaviorally relevant information for the animal is not just the position along the track but also the way in which it is facing; for example this determines how far away a potential reward is, if located at one or both ends of the track. Studies using periodic tracks have shown no such global remapping, but rather some degree of rate remapping ( Schwindel et al, 2016 ), that is the direction of motion affects the shape and amplitude of place fields, but not their position. In the data we have analyzed there is very weak remapping, see Figure 7—figure supplements 1c and 2b , and so the assumption of invariance of place field to direction of motion is a good one.…”
Section: Discussionmentioning
confidence: 99%
“…As we could not explain this effect based on changes in behavioral variables, this suggests a certain amount of trial‐unique content, as has been shown previously with different analyses (Manns et al, ; Mankin et al, ; Ziv et al, ). If the contribution of time, or trial‐unique features more generally, to internally generated sequences is large (Takahashi, ; Schwindel et al, ), then averaging across many trials may limit and/or bias the detection of trial‐specific replay content. As it is not yet clear to what extent internally generated sequences reflect trial‐unique experience, it is difficult to convert this possibility into specific recommendations when interpreting decoded replay data.…”
Section: Discussionmentioning
confidence: 99%
“…As we could not explain this effect based on changes in behavioral variables, this suggests a certain amount of trial-unique content, as has been shown previously with different analyses (Manns et al, 2007; Mankin et al, 2012; Ziv et al, 2013). If the contribution of time, or trial-unique features more generally, to internally generated sequences is large (Takahashi, 2015; Schwindel et al, 2016), then averaging across many trials may limit and/or bias the detection of trial-specific replay content. As it is not yet clear to what extent internally generated sequences reflect trial-unique experience, it is difficult to convert this possibility into specific recommendations when interpreting decoded replay data.…”
Section: Discussionmentioning
confidence: 99%